2014
DOI: 10.1039/c3lc50866h
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of subcellular morphology of single yeast cells using high frequency microfluidic impedance cytometer

Abstract: Single-cell impedance cytometry is an electrical analysis method, which has been used to count and discriminate cells on the basis of their dielectric properties. The method has several advantages, such as being label free and requiring minimal sample preparation. So far, however, it has been limited to measuring cell properties that are visible at low frequencies, such as size and membrane capacitance. We demonstrate a microfluidic single cell impedance cytometer capable of dielectric characterization of sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 31 publications
(35 reference statements)
2
67
0
Order By: Relevance
“…below the range of the -dispersion) is similar to that of an insulating particle (e.g. Schade-Kampmann et al (2008), Haandbaek et al (2014)). The method is also promising for nonspherical particles or cells because, although the latter yield impedance signals depending on their orientation (Jones 1995;Fernandez et al 2017), the transit times and the relative prominence are not significantly affected by particle orientation.…”
Section: Resultsmentioning
confidence: 74%
“…below the range of the -dispersion) is similar to that of an insulating particle (e.g. Schade-Kampmann et al (2008), Haandbaek et al (2014)). The method is also promising for nonspherical particles or cells because, although the latter yield impedance signals depending on their orientation (Jones 1995;Fernandez et al 2017), the transit times and the relative prominence are not significantly affected by particle orientation.…”
Section: Resultsmentioning
confidence: 74%
“…However, most DS efforts, as well as electromechanical methods that also exploit cell electrical properties (e.g., electrophoresis (DEP) and electrorotation [8], [9]), operate at relatively low frequencies. High frequencies are expected to be necessary to probe cell interiors [10], [11] while broad frequency coverage is essential to uncover cell characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The convolution of these effects currently limits the ability of the system in distinguishing between single or budded cells, and small cell clusters. Other studies have shown that optimized geometries and setups, featuring multiple facing and focusing electrodes, provide the capability to distinguish between different cell clusters 26 or to analyze intra-cellular features 41 . However, integration of complex sensing structures, such as sandwich structures 41 or electrode posts perpendicular to substrate plane 42 , into the current setup would increase device complexity and compromise ease of cell loading, culturing, and imaging.…”
Section: Impedance Measurements Of Cellsmentioning
confidence: 99%
“…Other studies have shown that optimized geometries and setups, featuring multiple facing and focusing electrodes, provide the capability to distinguish between different cell clusters 26 or to analyze intra-cellular features 41 . However, integration of complex sensing structures, such as sandwich structures 41 or electrode posts perpendicular to substrate plane 42 , into the current setup would increase device complexity and compromise ease of cell loading, culturing, and imaging. The current setup meets the requirements for measuring cell growth rates and changes in those, as the passage of clustered cells over the electrodes happened very rarely, as has been confirmed with microscopy observations.…”
Section: Impedance Measurements Of Cellsmentioning
confidence: 99%